Geology, geochemistry and petrotectonic setting of Idanre Granite Complex, Southwestern Nigeria / Akinola Oluwatoyin Olagoke - Akinola Oluwatoyin , Olagoke (2020)
During Neoproterozoic, Nigeria like many other Pan-African countries witnessed extensive magmatic activities which resulted in emplacement of granite popularly referred to as Older Granite in Nigeria. The study area is characterized by a large population of this rock type than any other part of Nigeria, so these rocks are investigated in this research. Idanre is underlain by migmatite-gneiss, charnockite and granite. Migmatite form the country rock and are low-lying, charnockite was surrounded by granite, while the granite forms large inselbergs. Three textural types of granite occur in the area, they are coarse-grained granite (undifferentiated) (OGu), porphyritic granite (OGp) and the fine-grained granite (OGf). Analytical results revealed the siliceous nature of the basement rocks, the range of silica contents are migmatite (55.90 - 65.32%), charnockite (60.62 - 63.70%) and granite (62.97 - 74.52%). Geochemical result also showed the granitoids range in composition from alkali granite to granodiorite, they are metaluminous ferroan I-type late orogenic suites with shoshonitic to high-K alkali calcic signatures. Na2O/Al2O3 versus K2O/Al2O3 diagram showed the protolith of the granite rocks have extensive data plot spread within igneous field revealing the granite originated from anatexis of igneous rocks. The occurrence of igneous structures like poikilitic textures, sphene and myrmekite are petrographic evidence of igneous origin for the granite. All the granites exhibit similar geochemical coherence between their trace elements distribution evidenced by similar shape for the chondrite normalized REE pattern. The gneiss units are also characterized by similar geochemical features. All the granite samples showed LREE enrichment, HREE depletion and plagioclase fractionation with evidence from negative Eu anomaly (Eu/Eu*<1). Geochemical appraisal revealed the granitoids are of “within-plate” tectonic setting. Zircon U-Pb geochronology showed migmatite with 1065.1 ± 7.1 Ma age represents the oldest rock in Idanre area. This was subsequently followed by charnockite (590.3 ± 5.3 Ma), fine-grained granite (588.4 ± 5.5 Ma) and porphyritic granite (584.5 ± 5.8 Ma) while the last magmatic episode produced the Undifferentiated granite (581.8 ± 5.5 Ma) which is the youngest member of the suite. 176Hf/177Hf ratios in OGu vary between 0.281724 and 0.281843 with initial 176Hf/177Hf between 0.281715 and 0.281782, ƐHf(t) values range between -22.2 to -23.5 and tDM2 age 2800 ~ 2990 Ma. 176Hf/177Hf ratios in OGp range between 0.281692 and 0.281863, initial Hf values between 0.281683 and 0.281848, ƐHf(t) values between -22.5 to -25.5, tDM2 age range between 2850 ~ 2950 Ma. In OGf, 176Hf/177Hf values range between 0.281712 to 0.281813 with initial values from 0.281708 to 0.281802, ƐHf(t) lies between -22.4 to -25.7 and tDM2 age 2880 ~ 3000 Ma. These tDM2 values all indicated that the inherited zircons were separated from the “Depleted Mantle” around 2.8 ~ 3.0 Ga. Negative ƐHf(t) values symbolized derivation from crustal source, while tDM2 age implied magma source originated during Mesoarchean.